The Implementation Concept Of "Learning Style Inventory" David Kolb Based PHP On STMIK Nusa Mandiri - Ramadan, Rino (Sinkron : jurnal dan penelitian teknik informatika, 2019)
The concept of "Learning Style Inventory" offered David Kolb is a concept for the assessment in detecting a person's learning style. The learning process is based on the experience of having 5 cycles. 5 of them can be used as a reference for the assessment. David Kolb has created 12 questions that can already be used as a reference in making this assessment. Question by David Kolb create an outline already refers to the cycle of learning from experience. After getting answers to 12 questions before, and then we do the calculation based on a formula created by David Kolb. The formula are consists of 4 score. The first score is CE (Concentrate Experience), then the second score is AE (Active Experimentation), then the third score is RO (Reflective Observation), and the final score is AC (Abstract conceptualization). The assessment process will do is add any weighting of each question and divided based on each option. Then we add up to 12 about the nominal weighting. Having obtained in total, we then perform the detection process of learning styles based on the concept of learning styles with the reference calculation by analysis David Kolb's learning style. The concept offered David Kolb has many implemented with a variety of versions, this time the writer will try to implement this concept to the programming language PHP along with supporters other programming language. By implementing these concepts based on PHP, then the respondent can conduct the assessment process whenever and wherever